Solving the problems of the current state of the agro-industrial market against the background of the main trends of its development - V. Krasnova; A. Fomenko (Вестник Северо-Кавказского федерального университета, 2022)
The current conjuncture of the world food market indicates an increase in the problems of hunger and social tension of the importing countries of agro-industrial products. Concern about the development of agricultural production is growing every year. This study identified the main trends in the development of the agro-industrial complex of the world and the Russian Federation, as well as its current state. The global agro-industrial market has a rather diverse character due to its differentiation on the grounds of geographical location, demographic status, natural and climatic conditions, the involvement of states in global supply chains, the level of technological development of agricultural holdings, etc. In turn, the agro-industrial complex of the Russian Federation is still largely influenced by external factors and is formed under the influence of the world market, an overview of which determines the main ways to solve the problems of current strategic development. Based on the analysis, the paper proposed key directions for the development of the agricultural sector of the Russian economy, as well as the behavior of enterprises in conditions of crisis and uncertainty.